Political Communication vs Cultural Approach to Society Related to the Handling of Covid-19 - Kaseem, Jounadi; Zhain, Aish; Deen, Kduoh Al (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
This study discusses political communication and cultural approach in handling the Covid-19 pandemic. Existing cases are taken into account along in the discussion of this paper to illustrate how measures like communication by political figure influence the Covid-19 mitigation. The cultural relevance of the COVID-19 community engagement message is critical to its effectiveness. Culture-insensitive communication may be seen in the COVID-19 case study as well as in the Ebola information being communicated. It is nevertheless important to recognize that a culture’s collection of signals regarding life experience may range from positive behaviours that should be promoted to negative practices that should be addressed